Alfabetização científica nos anos iniciais do ensino fundamental: uma proposta articulada à literatura infantil - Bonini, Aline Patrícia Pasqui (2023)
This research aims to develop and analyze an Investigative Teaching Sequence relating Science teaching to literary text reading as a possibility to develop Scientific Literacy in the early years of Elementary School. The activities were planned from the content “property of materials” related to chemistry and on the tale “The Three Little Pigs” which were applied for third graders in Elementary School. This study has a qualitative feature, and the data gathering was carried out from the transcription and analysis of the students’ words during the application of SEI in a city public school in Limeira – SP. The classes were held on June 10, 13 and 14, 2022, requiring a total of 10 class hours. The planned activities were built from the structuring axes of Scientific Literacy (SASSERON, 2008) and rely on the elaboration of processes of investigative teaching, aiming at the students´ ability to mobilize, use and take decisions based on scientific knowledge taking into account situations related to reality and to everyday aspects. Therefore, it is noted that there is a contribution of the investigative feature activities that articulate two fields, science and literature, whereas it is possible to identify indicators of Scientific Literacy and realize the possibility of interconnection of these two areas, as both literature and science can relate to daily routine. providing several reflections on political, social and environmental aspects.